DHX36 prevents the accumulation of translationally inactive mRNAs with G4-structures in untranslated regions - Markus Sauer (Nature Portfolio, 2019)
Translation efficiency can be affected by mRNA stability and secondary RNA structures. Here the authors reveal that loss of DHX36 helicase activity leads to an accumulation of translationally inactive target mRNAs with G-rich structures in untranslated regions.